LKB1/AMPK/mTOR Signaling Pathway in Non-small-cell Lung Cancer - Han, Dong; Li, Shao-Jun; Zhu, Yan-Ting; Liu, Lu; Li, Man-Xiang (Asian Pacific journal of cancer prevention : APJCP, 2013)
Links between cancer and metabolism have been suggested for a long time but compelling evidence for this hypothesis came from the recent molecular characterization of the LKB1/AMPK signaling pathway as a tumor suppressor axis. Besides the discovery of somatic mutations in the LKB1 gene in certain type of cancers, a critical emerging point was that the LKB1/AMPK axis remains generally functional and could be stimulated by pharmacological molecules such as metformin in cancer cells. In addition, AMPK plays a central role in the control of cell growth, proliferation and autophagy through the regulation of mTOR activity, which is consistently deregulated in cancer cells. Targeting of AMPK/mTOR is thus an attractive strategy in the development of therapeutic agents against non-small-cell lung cancer (NSCLC). In this review, the LKB1/AMPK/mTOR signaling pathway is described, highlighting its protective role, and opportunities for therapeutic intervention, and clinical trials in NSCLC.